2010
DOI: 10.1111/j.1365-246x.2010.04803.x
|View full text |Cite
|
Sign up to set email alerts
|

Surface subsidence induced by the Crandall Canyon Mine (Utah) collapse: InSAR observations and elasto-plastic modelling

Abstract: S U M M A R YThe Crandall Canyon Mine, Utah, collapse in 2007 August resulted in a total of nine fatalities. We processed data from the ALOS satellite acquired before and after the collapse to quantify surface subsidence associated with the collapse to better understand the collapse process. The deformation shows a steep V-shaped pattern of subsidence with slight asymmetry. We compare the fit of four different models that simulate the subsidence pattern. The first two models use elastic half-space rheology. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“…The feature was approximately 1 km in diameter and showed a displacement of ~--0.30 m peak vertical (converted from the line--of--sight range change and assuming pure vertical motion). This is in good agreement with the spatial extent and amplitude reported by Plattner et al [2010] for the 8 June 2007- 8 Sept. 2007 pair although the exact details differ slightly. The 8 June --8 Sept 2007 pair was also processed in this study but showed higher decorrelation, which may have been due to the longer baseline and high elevations.…”
Section: Crandall Canyonsupporting
confidence: 81%
See 2 more Smart Citations
“…The feature was approximately 1 km in diameter and showed a displacement of ~--0.30 m peak vertical (converted from the line--of--sight range change and assuming pure vertical motion). This is in good agreement with the spatial extent and amplitude reported by Plattner et al [2010] for the 8 June 2007- 8 Sept. 2007 pair although the exact details differ slightly. The 8 June --8 Sept 2007 pair was also processed in this study but showed higher decorrelation, which may have been due to the longer baseline and high elevations.…”
Section: Crandall Canyonsupporting
confidence: 81%
“…Although Crandall Canyon is not a UCG operation, it is useful to examine as a proof of the concept. The collapse occurred during room and pillar operations at a depth of about 600 m in a seam with a thickness of about 2.4 m. Plattner et al, [2010] conducted modeling of the signal using a variety of methods and concluded that elasto--plastic collapse of an elliptic cavity provided the best fit to the data. Seismic data was also considered.…”
Section: Crandall Canyonmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus far, Plattner et al [15] and Ismaya and Donovan [16] estimated a part of parameters of the 0196-2892 © 2016 IEEE. Personal use is permitted, but republication/redistribution requires IEEE permission.…”
Section: Insar-based Model Parameter Estimation Of I Introductionmentioning
confidence: 99%
“…Repeat pass Interferometric synthetic Aperture Radar (InSAR) is a powerful tool for subsidence mapping [10][11][12][13]. For river delta studies, InSAR has previously been used to measure subsidence due to sediment consolidation and artificial loading in several deltas, including the Pearl River [14], Nile [15] and Fraser River [16] deltas.…”
Section: Introductionmentioning
confidence: 99%